Should we stop screening for chronic endometritis?. Issue 1 (January 2023) - Darici, Ezgi; Blockeel, Christophe; Mackens, Shari
ABSTRACT: Chronic endometritis is a poorly understood infectious or inflammatory process, potentially disrupting the correct implantation of a human embryo (Puente et al., 2020 ). The exact prevalence is a subject of discussion and ranges across the available literature from 2% to almost 60%, with a higher suspicion of the condition being present in women with recurrent early pregnancy loss and recurrent implantation failure (Puente et al., 2020 ). The impact of chronic endometritis on reproductive outcomes following IVF remains questionable given the lack of proper data convincingly showing an improvement after diagnosis and treatment. This article aims to provide the reader with a critical appraisal of current diagnostic methods, treatments and patient populations to be tested for chronic endometritis.